A scoping review on the intrinsic & extrinsic vision-related factors in driving / Chen Ai-Hong ... [et al.] - Chen, Ai-Hong; Chik, Nur Adilah; Noor Azman, Nur Qamarina; Abd Aziz, Aisyah Nabilah; Ruslan, Fazilatul Az-Zahrah (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Driving performance can be influenced by multiple factors. The intrinsic factors encompass age, gender, visibility, visual field and movement patterns of the driver. The extrinsic factors cover road signage, lane, streetlight, weather and time of the day. Driving is undisputedly a highly visual task. The visibility of drivers can be affected by visual acuity, contrast sensitivity, illumination and glare issues. Contrast sensitivity is a better predictor of driving performance than visual acuity. Driving performance downgrades with increasing blur. Uncorrected refractive error reduces the distance to recognize road signs and increases driving time. Central visual field defect displays more difficulty in driving performance compared to peripheral visual field defects. Binocular visual field defects have more severe impacts on driving performance. Homonymous hemianopia is considered not safe for driving. The impacts of altitudinal visual field defects and scotoma remain inconclusive. Driver's movement patterns have been employed in various driving research to indicate distraction and engagement. Eye, head, and body movements are closely linked to driving behaviours. The legibility of the road sign is essential to provide a safer road environment for road users. The road signs should be legible sufficiently far away to give advanced notice to road users. Appropriate spacing and positioning of lanes and streetlights are crucial for safe daytime and night-time driving.